Flood model Bergen Norway and the need for (sub-)surface INnovations for eXtreme Climatic EventS (INXCES). (2017) - Boogaard, Floris; Kluck, Jeroen; Bosscher, Michael; Schoof, Govert
Abstract: Urban flooding has become a key issue for many cities around the world. The project 'INnovations for eXtreme Climatic EventS' (INXCES) developed new innovative technological methods for risk assessment and mitigation of extreme hydroclimatic events and optimization of urban water-dependent ecosystem services at the catchment level. DEMs (digital elevation maps) have been used for more than a decade now as quick scan models to indicate locations that are vulnerable to urban flooding. In the last years the datasets are getting bigger and multidisciplinary stakeholders are becoming more demanding and require faster and more visual results. In this paper, the development and practical use of DEMs is exemplified by the case study of Bergen (Norway), where flood modelling using DEM is carried out in 2017 and in 2009. We can observe that the technology behind tools using DEMs is becoming more common and improved, both with a higher accuracy and a higher resolution. Visualization tools are developed to raise awareness and understanding among different stakeholders in Bergen and around the world. We can conclude that the evolution of DEMS is successful in handling bigger datasets and better (3D) visualization of results with a higher accuracy and a higher resolution. With flood maps the flow patterns of stormwater are analysed and locations are selected to implement (sub-)surface measures as SuDS (Sustainable Urban Drainage systems) that store and infiltrate stormwater. In the casestudy Bergen the following (sub-)surface SuDS have been recently implemented with the insights of DEMS: settlement storage tank, rainwater garden, swales, permeable pavement and I/T-drainage. The research results from the case study Bergen will be shared by tools to stimulate international knowledge exchange. New improved DEMs and connected (visualization) tools will continue to play an important role in (sub-)surface flood management and climate resilient urban planning strategies around the world.